Introducing youth mobility and migration - Cairns, D.; Cuzzocrea, V.; Krzaklewska, E. (The Palgrave handbook of youth mobility and educational migration, 2022)
The aim of this chapter is to introduce some of the conceptual tools researchers have developed to help explain young people’s spatial movement, especially in education, work and training contexts. This includes a reappraisal of the relationship between mobility and migration, seeing them as nested practices rather than distinct. The chapters also discuss how mobility is imaginatively integrated into life planning, with moving abroad while young potentially initiating a migration trajectory. This work is, we hope, an appropriate starting point for this book in establishing a starting point for mobility and arguing that what happens in the youth phase has lasting value.